STRUCTURAL PROPERTIES OF NITROGEN DOPED ANATASE AND RUTILE TiO2 THIN FILMS - Aijaz, Asim; Uddin, Zaheer; Siddiqui, Imran Ahmad (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Anatase and rutile TiO2 thin films have been doped by N ion implantation. The effect of N doping on the structural changes of TiO2 thin films and its correlation to the optical and chemical properties of the films is investigated. The depth and concentration of the implanted N atoms is found not to exhibit substantial difference for anatase and rutile phases. The energy loss of the implanted N atoms correlates well to the energy gained by O and Ti atoms in the TiO2 lattice. An increased number of O vacancies are found to be generated as compared to Ti for both anatase and rutile phases. The energy loss mechanisms of the implanted N atoms together with the O vacancy generation are found to be the major driving forces for facilitating enhanced optical and chemical properties of the TiO2 thin films.